Transcatheter mitral valve repair in patients with chronic liver disease: Insights from the national inpatient sample. Issue 2 (8th August 2020) - Khan, Muhammad U.; Khan, Muhammad Z.; Khan, Safi U.; Kaluski, Edo
Abstract: Objective: To evaluate contemporary national trends of morbidity, mortality, and healthcare utilization in patients with mitral regurgitation (MR) and co‐existing chronic liver disease (CLD) undergoing transcatheter mitral valve repair (TMVR). Methods: The National Inpatient Sample (NIS) was used to assess trends in patients undergoing TMVR between January 2012 and December 2017. Propensity match analysis was done to compare it to subjects without underlying CLD. Logistic regression analysis was used to identify predictors of in‐hospital mortality. Results: Of 15, 270 patients undergoing TMVR, 569 (3.7%) had coexisting CLD. Patients with CLD had a higher proportion of males (61.3 vs 52.6%; p < .01), congestive heart failure (6.9 vs 1.0%; p < .01), renal failure (42.2 vs 36.7%; p < .01), and peripheral vascular disease (19.3 vs 12.5%; p < .01). After propensity matching subjects with CLD had significantly higher hospital mortality (19.8 vs 4.6%; p < .01), acute kidney injury (46.1 vs 37.8%; p < .01), cardiogenic shock (25.4 vs 12.1%; p < .01), mechanical ventilation (26.3 vs 14.0; p < .01), pneumothorax (6.6 vs <2%.; p < .01), length of stay (5 vs 9 days), and average cost of hospitalization (209, 573 vs 250, 587 ; p < .01). Over the years, in‐hospital mortality in patients receiving TMVR has improved in both patients with (from 33.3 in 2013 to 22.2% in 2017) and without CLD (from 2.7 in 2011 to 1.6% in 2017). Conclusion: Patients with MR undergoing TMVR, with coexisting CLD bear substantially higher comorbidities, complication rates, and inpatient mortality compared with those without CLD. A favorable temporal trend of in‐hospital mortality among these subjects is noteworthy.